Flower election by honeybee and floral morphology - de Sá Otero, María Pilar; Díaz Losada, Emilia; Armesto Baztán, Sandra (Lazaroa, 2004)
The aim of this research was to determine which are the Apis mellifera L. preferences in iheir choosing of pollen sources. The relative importance of the corolla colour and shape, presence or absence of floral nectaries in the visited flowers, and the chosen plant species relative abundance were studied in hives located in northwest Spain. The corbicular pollen carried to the hive by the honeybee was studied in this research work. The results of pollen analysis tested through non-parametric statistic studies. Yellow was confirmed as the preferred colour together with white, both by the diversity of the visited species that have these characteristics and the amount of pollen collected from them. The presence of floral nectaries is now a decisive factor in the selection of plant sources for pollen.